EFEKTIVITAS PELAKSANAAN REHABILITASI TERHADAP KORBAN PENYALAHGUNAAN NARKOTIKA DI SAMARINDA - Andari, Soetji (Babes Litbang Yankessos, 2019)
The province of East Kalimantan was ranked the fifth highest drug trafficking in Indonesia in 2018. BNNP East Kalimantan has processed 115 suspects to be submitted to prosecution in court with the most evidence of methamphetamine type drugs most affected are young people. Research on efforts to prevent the distribution of illicit substances carried out at the Laras and Sekata Forbidden Substance Concern Foundation in Samarinda City, East Kalimantan, is an evaluation research carried out by combining quantitative (primary) methods with qualitative (support) methods. The techniques used in the evaluation activities are observation, questionnaires, interviews, document studies and Focussed Group Disscusion techniques. Data collection was carried out on 60 respondents. Results of the study Understanding of resident families in social rehabilitation services for victims of substance abuse in the Laras IPWL and Sekata Samarinda IPWL seen from the input component seen from the procedures for in the high category or in the very good category (97.00%). This result is supported by the presence of sufficiently competent human resources in the implementation of social rehabilitation for victims of illicit substances, the implementation has referred to general guidelines and technical guidelines. Peers 'understanding of social rehabilitation services for illicit victims of prohibited substances is viewed from the context of context, namely residents' understanding of the existence of IPWL at a very understanding level of 87.00%. Peer understanding of social rehabilitation services for illicit victims of prohibited substances is viewed from the input aspect, which is related to the availability of facilities and infrastructure, human resources, and funds at IPWL according to residents in the very good category at 97.00%. Peer understanding of social rehabilitation services for illicit victims Forbidden substances are reviewed from the aspect of the process namely the social rehabilitation service for abusing victims at an effective level of 80.00%.